Analysis of the Effect of Work-Family Conflict, Work Stress, and Job Satisfaction on the Performance of BPK-RI Auditors in West Sumatra - Fadhilah, Rahmi; Lukito, Hendra; Games, Donard (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Recent demographic changes have seen an increase in dual-income households, with partners working for financial stability but often sacrificing their role in the household. This suggests the need for greater support from organizations in the modern family structure. As an institution that audits the financial statements of public institutions in Indonesia, the quality of BPK-RI audits has a direct impact on the accountability and transparency of state finances. BPK-RI auditors face significant challenges, such as balancing workloads with family responsibilities and high levels of stress that can potentially interfere with employee performance. The purpose of this study was to investigate the effect of work-family conflict and job stress on auditor performance with job satisfaction as a mediating variable in the study at BPK-RI West Sumatra. This study used primary data from filling out questionnaires, which were analyzed using the SEM-PLS method. The results showed that work-family conflict had a positive and significant effect on performance, and job satisfaction could be a mediating variable in the relationship between work-family conflict and performance. Conversely, job stress did not affect performance and job satisfaction could not be a mediating variable in the relationship between work-family conflict and performance.